STRUKTUR MODAL DAN KEPUTUSAN INVESTASI PADA PERUSAHAAN TELEKOMUNIKASI INDONESIA - Palti Marulitua Sitorus; D.S. Priyarsono D.S. Priyarsono; Adler Haymans Manurung; Tubagus Ahmad Maulana (Jurnal Keuangan dan Perbankan, 2014)
This study aimed to explore the interconnection of capital structure and investment decisions based on therelationship between corporate leverage and investment options. The samples used were telecommunicationcompanies in Indonesia which had already become public companies from 2006 to 2013. The data was processedby using multiple regression technique and t test and F test to see the difference of investment source.This study revealed that an increase in the firm value as a result of an increase in the debts of the company andits increase was different between the companies that the investment came from foreign investment and localinvestment. Investment selection by using the debt was considered to be the correct choice made by management.The value of the company was obtained better by companies that used local investment. Telecommunicationbusiness was still considered by investors to be the prospective industries.